Sarcospan-Deficient Mice Maintain Normal Muscle Function - Lebakken, Connie S. (American Society for Microbiology, 2000)
Sarcospan is an integral membrane component of the dystrophin-glycoprotein complex (DGC) found at the sarcolemma of striated and smooth muscle. The DGC plays important roles in muscle function and viability as evidenced by defects in components of the DGC, which cause muscular dystrophy. Sarcospan is unique among the components of the complex in that it contains four transmembrane domains with intracellular N- and C-terminal domains and is a member of the tetraspan superfamily of proteins. Sarcospan is tightly linked to the sarcoglycans, and together these proteins form a subcomplex within the DGC. Stable expression of sarcospan at the sarcolemma is dependent upon expression of the sarcoglycans. Here we describe the generation and analysis of mice carrying a null mutation in the Sspn gene. Surprisingly, the Sspn-deficient muscle maintains expression of other components of the DGC at the sarcolemma, and no gross histological abnormalities of muscle from the mice are observed. The Sspn-deficient muscle maintains sarcolemmal integrity as determined by serum creatine kinase and Evans blue uptake assays, and the Sspn-deficient muscle maintains normal force and power generation capabilities. These data suggest either that sarcospan is not required for normal DGC function or that the Sspn-deficient muscle is compensating for the absence of sarcospan, perhaps by utilizing another protein to carry out its function.